Perencanaan Bauran Pembangkit Listrik Energi Terbarukan di Indonesia: Pendekatan Optimasi Program Linier Berbasis Wilayah - Garmaisa, Annisa; Wikarya, Uka (Jurnal Kebijakan Ekonomi, 2025)
Indonesia has renewable energy potential spread across various islands. However, limited interconnection between regions is an obstacle to energy distribution. The purpose of this study is to analyze the planning of renewable energy (RE) power plants covering eight types: Geothermal Power Plants (PLTP), Solar Power Plants (PLTS), Wind Power Plants (PLTB), Biomass Power Plants (PLTBm), Biogas Power Plants (PLTBg), and Waste Power Plants (PLTSa). The analysis was conducted in four main system regions in Indonesia, namely Java-Bali, Sumatra, Kalimantan, and Sulawesi, which are currently not interconnected. The study is based on the availability of renewable energy potential, production forecasts, and installed capacity in Indonesia in 2022. The linear programming method is used to allocate renewable energy potential to minimize generation costs or LCOE (Levelized Cost of Electricity). The results of the study show that the Java-Bali, Kalimantan, and Sulawesi regions can achieve the renewable energy mix target of 34% of total generation in 2030. Meanwhile, the Sumatra region is projected to be able to achieve the renewable energy mix target of 46% in the same year. Furthermore, all regions are projected to achieve 100% renewable energy mix by 2050. The development of PLTS and PLTM/MH is a top priority due to its large potential and low LCOE, with a scale and time adjusted to regional needs.